Prophetic Approach: Initiating an Alternative Pedagogic Theory - Syihabuddin, Syihabuddin (INSANCITA, 2016)
ABSTRACT: Allah is the ultimate educator of this world (rabbu al-âalamin), including human beings. The results of His theistic education are in the forms of knowledge and various resources contained in humansâ souls. Then, He sent the Prophet to externalize the knowledge and resources into behaviors through Prophetic approach (al-Nubuwwah). This approach involves the following stages: tilawah, tazkiyah, and taâlim. âTilawahâ is practiced through reading, examining, and studying the verses of Allah revealed in this world, as summarized in âSunnatullahâ, thus producing conclusions, theories, and knowledge. The process and results of the data (the verses) are then developed, internalized, and corrected through âtazkiyahâ. This second stage prepares human beings to be ready to study life by combining dogmatic knowledge (al-Kitab) and the abstraction of their lives (al-Hikmah). This is the result of the third stage of the Prophetic approach, namely âtaâlimu al-kitabi wa al-hikmahâ. This article examines on those Prophetic approaches. Although the Prophetic approach is still in a conceptual stage, however, I invite teachers and educators to present this idea in the classrooms. We do not have to wait until this idea is elaborated in an operational lesson plan, but we can start from ourselves and from now. If we start learning activities, for example, we should present the intent only for worshipping Allah SWT. If we want to educate in that way, in fact, we have commenced a Prophetic approach.KEY WORD: Prophetic Approach; Tilawah; Tazkiyah; Taâlim; Theory and Implementation.Â ABSTRAKSI: âPendekatan Profetik: Perbincangan Awal Ihwal Teori Pedagogik Alternatifâ. Allah SWT (Subhanahu Wa-Taâala) adalah pendidik hakiki atas alam semesta (rabbu al-âalamin), termasuk manusia. Hasil pendidikan theistik ini ialah tersimpannya ilmu pengetahuan pada berbagai makhluk dan pada jiwa manusia. Kemudian Allah SWT mengirimkan Rasul untuk mengeksternalisasi ilmu pengetahuan tersebut, menjelaskannya dalam berbagai konteks, dan mencontohkannya dalam kehidupan nyata. Inilah yang disebut pendekatan Profetik, yang berlangsung dalam tiga tahap: tilawah, tazkiyah, and taâlim. âTilawahâ dilakukan melalui kegiatan membaca, menelaah, dan mempelajari ayat-ayat yang dibentangkan Allah SWT pada alam semesta. Ayat-ayat tersebut disimpulkan dalam konsep Sunnatullah, yang merupakan serangkaian rumusan kesimpulan, teori, dan ilmu pengetahuan. Selanjutnya, hasil pengolahan data berupa ayat-ayat Tuhan itu dikembangkan, diinternalisasikan, dan dikoreksi melalui proses âtazkiyahâ. Tahap Profetik yang kedua ini bertujuan menyiapkan manusia agar dia berkesiapan untuk mempelajari kehidupan dengan memadukan antara pengetahuan dogmatik (al-Kitab) dengan nilai-nilai dan pengalaman kehidupan (al-Hikmah). Ini adalah hasil ketiga dari pendekatan Profetik, yaitu âtaâlimu al-kitabi wa al-hikmahâ. Artikel ini mengkaji tentang pendekatan Profetik. Walaupun pendekatan Profetik ini masih dalam tahapan konseptual, walau bagaimanapun, saya mengajak para guru dan pendidik untuk menyajikan gagasan ini didalam kelas. Kita tidak harus menunggu sampai gagasan ini dielaborasi dalam bentuk rencana pembelajaran yang operasional, namun kita dapat melalui diri kita sendiri dan memulainya sekarang. Jika kita memulai kegiatan pembelajaran, misalnya, kita hendaknya bertujuan semata-mata untuk beribadah kepada Allah SWT. Jika kita mau mendidik dengan cara seperti itu, pada kenyataannya, kita telah memulai pendekatan Profetik ini.KATA KUNCI: Pendekatan Profetik; Tilawah; Tazkiyah; Taâlim; Teori dan Implementasi.About the Author: Prof. Dr. Syihabuddin is Full Professor at the Department of Arabic Language Education, Faculty of Language and Literature Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Corresponding author is: syihab_upi@yahoo.co.idHow to cite this article? Syihabuddin. (2016). âProphetic Approach: Initiating an Alternative Pedagogic Theoryâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.1(2), August, pp.137-150. Bandung, Indonesia: Minda Masagi Press, ISSN 2443-1776. Chronicle of the article: Accepted (March 16, 2016); Revised (June 1, 2016); and Published (August 30, 2016).